Integrating Character Education in Teaching English - Rindi Tri Fardita; Tahrun Tahrun; Mulyadi Mulyadi (Universitas Pahlawan Tuanku Tambusai, 2022)
In Indonesia, English has become a lesson that must be learned and has many enthusiasts. However, can English lessons be used to integrate character education. This descriptive qualitative method research aims to find about character education that can be integrate in teaching English, teaching materials that can be used and how the teachers integrate character education in teaching English. This research was conducted at Junior High School 4 of Tungkal Jaya. Informants of this research were English teachers and students at grade eight. The data obtained from observation, interview and documentation and analyzed using a qualitative analysis process by using data reduction, display and conclusion. Findings of this research showed that: there are only eight characters education that can be integrated in teaching English, this eight characters education were integrated by using teaching material “One Direction song, History which tells about togetherness and friendship” and integrated by carry out teaching in accordance with the existing syllabus and lesson plans. This research provide information to English teachers about the integrating of character education in teaching activities.